Do Perceived Organizational Justice and Trust Determine Satisfaction of Performance Appraisal Practice? A Case of Malaysian Secondary School teachers. - Bin Abdullah, Abdul Ghani Kanesan; Anamalai, Thiagarajan a/l; Ismail, Aziah bt; Ling, Ying-Leh (Advances in Social Sciences Research Journal, 2015)
The purpose of this study is to investigate the organizational justice and trust as the determinant of satisfaction in teachers’ performance appraisal system. This study was carried out by using survey method. In this research, this questionnaire was administered to 714 teachers from 102 secondary public schools in the Northern Region of West Malaysia. The data were analyzed by “Hierarchical Moderated Multiple Regression Analytical Procedures” (HMMR), using the statistical package program (SPSS15.0). As a result, it is revealed that the organizational justice (distributive, procedural, interpersonal) poses a positive influence on the performance appraisal satisfaction. Elevating the degree of trust and satisfaction among teachers towards the performance appraisal, and creating a conductive environment for teachers to improve their performance are the best strategies to achieve teacher’s performance appraisal satisfaction.